Современное состояние гнездовий большого баклана (Phalacrocorax carbo) на водно-болотном угодье Молочный лиман - Черничко, Р.Н. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2008)
Materials for this work were collected during long-term investigations of birds of the Molochnyi Liman, carried out by ornithologists of the Melitopol State Pedagogical University and the Azov-Black Sea Ornithological Station in 1987-2008. Within the Molochnyi Liman area the Cormorant has nested for the first time on Kirillovskie Islands, later its main nesting-places moved to Podkova and Dolgiy Islands, and since 2005 the birds returned to Kirillovskie Islands again.